1999
DOI: 10.1183/09031936.99.13351499
|View full text |Cite
|
Sign up to set email alerts
|

Empirical treatment with fibrinolysis and early surgery reduces the duration of hospitalization in pleural sepsis

Abstract: Empirical treatment with fibrinolysis and early surgery reduces the duration of hospitalization in pleural sepsis. T.K. Lim, N.K. Chin. #ERS Journals Ltd 1999. ABSTRACT: The efficacy of three different treatment protocols was compared: 1) simple chest tube drainage (Drain); 2) adjunctive intrapleural streptokinase (IP-SK); and 3) an aggressive empirical approach incorporating SK and early surgical drainage (SK+early OP) in patients with pleural empyema and high-risk parapneumonic effusions.This was a nonrandom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
1
5

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 24 publications
2
43
1
5
Order By: Relevance
“…We also found that hospitalization was significantly longer in patients requiring pleural drainage or decortication. This fi nding contrasts with other publications in which decreases in hospital stay were registered after surgical treatment with or without associated instillation of intrapleural fi brinolytics [18][19][20] . The reason for this difference may reside in the fact that decortication was performed earlier in these previous publications, whereas in our patients it was done after other therapies had failed (median 22.6 days).…”
Section: Discussioncontrasting
confidence: 54%
“…We also found that hospitalization was significantly longer in patients requiring pleural drainage or decortication. This fi nding contrasts with other publications in which decreases in hospital stay were registered after surgical treatment with or without associated instillation of intrapleural fi brinolytics [18][19][20] . The reason for this difference may reside in the fact that decortication was performed earlier in these previous publications, whereas in our patients it was done after other therapies had failed (median 22.6 days).…”
Section: Discussioncontrasting
confidence: 54%
“…The six-dose regimen, in which a total of 1.5 million units of streptokinase is administered, represents more doses and a larger total dose of the drug than the regimens used in earlier studies examining intermediate surrogate end points, which had positive results. 8,10,13 Finally, the overall combined rate of death or the need for surgery was similar to that in previous studies, 2,5,16,17 suggesting that our study population was representative.…”
Section: Subgroup Analysessupporting
confidence: 70%
“…According to studies, early surgical intervention (VATS or thoracotomy) can reduce complication rates and shorten healing process in the following clinical conditions: patients without clinical improvement despite tube drainage or tube and IPFT treatment; those with persistent fever and leukocytosis; patients with ongoing loculations in the imaging; and those without any improvement in the amount of pleural fluid (2,3,16,17,18). In our study, we applied decortication to 3 and VATS to 4 patients.…”
Section: Discussionmentioning
confidence: 99%